The Development of Daily-life English Speaking Skill for Communication with CIPPA Model with 4MAT Learning Management Model and Multiple Intelligence Activities of Mattayomsuksa5 Students - Chuanram, Yada; Koram , Tassawin; Hormjarn , Suchart; Silpakob , Korakoch; Wattanasuk, Sineenat (Mahachula Academic Journal, 2026)
The purposes of this research were: (1) to compare abilities in daily-life English speaking for communication of Mattayomsuksa5 Students before and after studying. (2) to study the Mattayomsuksa5 students’ satisfaction toward CIPPA Model with 4MAT Learning Management Model and Multiple Intelligence Activities. The sample consisted of 17 Mattayomsuksa5 students that were studying in the second semester of the academic year 2023 selected by cluster sampling. The employed statistics were percentage, mean, standard deviation and dependent t-test. The research results revealed as follows; 1) abilities in daily-life English speaking for communication of Mattayomsuksa5 Students after using the CIPPA Model with 4MAT Learning Management Model and Multiple Intelligence Activities was higher than before studying at statistical significance of 0.05 level, and 2) the students’ satisfaction toward the CIPPA Model with 4MAT Learning Management Model and Multiple Intelligence Activities was at the most level with the mean value of 4.68 and standard deviation value of 0.62.